Visual Studio 2010, SMS Gateway, IMPLEMENTASI SMS GATEWAY MENGGUNAKAN VISUAL STUDIO 2010 UNTUK PELAYANAN KONSELING JEMAAT - Hartini, Hartini Tini (Universitas Putera Batam, 2020)
Now SMS can be used for various applications, such as Mobile Banking, Interactive Pooling, and others. SMS is also very useful in the Bethany Kuala Kapuas church, one of which is used as a congregation counseling system. Because the counseling schedule between the counselor and the church is not yet efficient. So that the counselor is a little overwhelmed with this, so an application is needed to arrange the counseling schedule. The way the congregation sends an SMS application and later the counselor who serves as an admin (in office hours) will reply to the SMS which contains counseling schedules with the congregation. The SMS Gateway based Church Counseling Service application at Bethany Kuala Kapuas Church was made using Visual Studio 2010 and AT + Commands as a command language that can be read by a modem. With this application it is expected to facilitate the congregation in delivering their counseling, thus helping the counselors to monitor easily